Autophagy as a mechanism of Apo2L/TRAIL resistance. Issue 9 (2nd September 2018) - Sharma, Arishya; Almasan, Alexandru
ABSTRACT: Apo2 ligand (Apo2L)/tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) is unique to selectively induce apoptosis in tumor cells while sparing normal cells. Thus there is tremendous interest in Apo2L/TRAIL therapy; however, drug resistance is a serious limitation. Autophagy is a cellular housekeeping process that controls protein and organelle turnover, and is almost consistently activated in response to apoptosis-inducing stimuli, including Apo2L/TRAIL. Unlike apoptosis, autophagy leads to cell death or survival depending on the context. Various molecular mechanisms by which autophagy regulates Apo2L/TRAIL-induced apoptosis have been identified. Further, whether autophagy is completed (intact autophagic flux) or not could determine the fate of cancer cells, either cell survival or death. Thus, targeting autophagy is an attractive strategy to overcome Apo2L/TRAIL resistance. We present the current view of how these regulatory mechanisms of this interplay between autophagy and apoptosis may dictate cancer cell response to Apo2L/TRAIL therapy.